Geographic distribution and phenotype of European people with cystic fibrosis carrying A1006E mutation. (February 2022) - Mondejar-Lopez, Pedro; Zolin, Anna; Garcia-Marcos, Patricia W.; Pastor-Vivero, Mª Dolores; Rosa-Silvestre, Maria; de Asis Sanchez-Martinez, Francisco; Salvatore, Donatello; Cimino, Giuseppe; Majo, Fabio; Sole-Jover, Amparo; Asensio de la Cruz, Oscar; Calderazzo, Maria Adelaide; et al.
Abstract: Background: A1006E is a Cystic Fibrosis (CF) mutation that is still not widely known. We report phenotypic features and geographic distribution of the largest cohort of people with CF (pwCF) carrying A1006E to date. Methods: Study of European pwCF carrying A1006E mutation, included in the European CF Society Patient Registry (ECFSPR). Genotype, ancestries and all variables recorded were compared to a cohort of F508del/F508del patients. Rate of decline in percentage-of-predicted FEV1 (ppFEV1 ) was also analyzed using the 2010–2017 ECFSPR. Results: 44 pwCF carrying A1006E were reported (59% males), median age 33 years old (3-58), 54.5% Spanish and 40.9% Italian, most with ancestry in Murcia (Spain) and Lazio (Italy) regions. Compared to F508del homozygous, A1006E-pwCF were significantly older (75% vs. 52.5% ≥ 18 years old) and diagnosed at later median age (6.98 vs. 0.29 years); showed lower rates of meconium ileus (2.33% vs. 17.7%), pancreatic insufficiency (27.91% vs. 99.26%), diabetes (2.33% vs. 21.98%), liver disease (6.98% vs. 36.72%) and Pseudomonas aeruginosa chronic colonization (30.95% vs. 42.51%); and presented better nutrition (BMI z-score 0.44 vs. −0.43) and ppFEV1 (90.8% vs. 78.6%), with 18.9% (most >40 years old) having a ppFEV1 <70%. Additional ppFEV1 decline (0.96% per year) was attributed to F508del/F508del genotype (p = 0.0007). None died or needed organ transplantation during the study period. Conclusions: A1006E-pwCF are mainly of Western Mediterranean Spanish and Italian descent. When compared with F508del/F508del-pwCF, they usually have a milder form of the disease, associated with pancreatic sufficiency and slower FEV1 decline. However, some will develop progressive respiratory impairment during adulthood. Highlights: A1006E is considered a rare CF-causing mutation worldwide. In 2017, there were 44 reported people with CF carrying the A1006E variant in Europe. Most of them lived in Spanish or Italian Mediterranean Regions. A1006E usually leads to milder CF, associated with pancreatic sufficiency. A1006E in cis should be investigated in subjects carrying 5T and/or V562I alleles.